Genomic and molecular characterization of a ceftazidime-avibactam resistant Klebsiella pneumoniae strain isolated from a Chinese tertiary hospital - Yanye Tu; Hui Gao; Feng Wang; Rongqing Zhao; Shiyong Chen; Yanzi Chang; Hong Li (BMC Microbiology)
Abstract Objective This study aims to investigate the molecular biological characteristics of a ceftazidime-avibactam resistant Klebsiella pneumoniae strain isolated from a tertiary care hospital in China. Methods The K. pneumoniae strain KP217360, isolated from a urine specimen at Li Huili Hospital affiliated with Ningbo University, was analyzed for antimicrobial susceptibility using the VITEK-2 Compact automated system. Antimicrobial susceptibility testing for polymyxin, tigecycline, and ceftazidime-avibactam was performed using broth microdilution according to CLSI guidelines. Whole genome sequencing was conducted using the Illumina platform, followed by comprehensive genomic analysis to characterize resistance determinants and virulence-associated genes. Experiments on conjugation were conducted to evaluate the transmissibility of the resistance plasmids. The virulence potential was evaluated through in vivo experiments using Galleria mellonella larvae as an infection model. Results The K. pneumoniae KP217360 strain demonstrated extensive antimicrobial resistance, showing non-susceptibility to imipenem, ertapenem and ceftazidime-avibactam. Genomic characterization revealed the strain belonged to capsular type KL16 and harbored multiple resistance determinants, including bla CTX−M−65, bla SHV−103 and bla TEM−1, along with iron acquisition-associated virulence factors (iutA, entABCDEF, and iroN). Plasmid analysis identified three distinct plasmids, among which an IncX3-type plasmid carrying bla NDM−5 was confirmed, while the functional characteristics of the remaining two plasmids require further investigation. In the Galleria mellonella infection model, the 72-hour post-infection survival rates significantly differed among groups (P < 0.001), with NTUH-K2044, KP217360 and ATCC700603 showing survival rates of 26.7%, 56.7% and 80%, respectively. Subsequent analysis using the Pathogen Host Interactions (PHI) database identified 1,349 genes in the KP217360 strain were expressed for reduced virulence. Conclusion This study reports the first identification of a ceftazidime-avibactam resistant K. pneumoniae ST685 strain carrying bla NDM−5 in Ningbo, Zhejiang Province, China. The findings underscore the urgent need for implementing comprehensive antimicrobial resistance surveillance programs and strengthening infection control measures to mitigate the dissemination of IncX3-type plasmids harboring bla NDM−5 in healthcare settings. Furthermore, our results emphasize the critical importance of establishing rapid enzymatic detection platforms in clinical microbiology laboratories to facilitate timely and precise therapeutic decision-making, thereby optimizing antimicrobial stewardship and improving patient outcomes.